Desempenho produtivo e efeito da vitamina C na qualidade nutricional e nos níveis de marcadores do estresse oxidativo em alevinos de tilápia-do-nilo (Oreochromis niloticus Linnaeus, 1857) - Menezes, Maria Emília da Silva (2010)
Vitamin C is used in the diets in order to improve growth, resistance to stress and disease, as well as the survival of fish. It can also be effective in the conservation of fish during processing and storage, inhibiting the degradation of lipids by oxidation. This study evaluated the stocking density and the effects of supplementation of vitamin C in the final quality of the fillet tilapia (Oreochromis nilotius, Linneaus, 1875). We used one hundred and twenty fingerlings for each trial, the study of fish stocking density had an initial weight of 4.0 g and evaluation of supplementation with vitamin C, 11.0 g. Both studies had a randomized design, comprising four treatments of different stocking densities (50, 75, 100 and 125 fish/m3) with five replications. Already working with vitamin C (ascorbic acid 2 - sulfate acid - protected form) was carried out in four treatments with six replicates, characterized by four levels of supplementation of vitamin C in the diets (250, 500 and 750 mg/kg diet) and control group (zero mg/kg diet) with two different stocking densities (50 and 100 fish/m3). The ration given to the first study contained 36% crude protein and 3100 kcal/DE/kg feed and the second was 28% crude protein and 3400 kcal/DE/kg. After ninety days, the fish were slaughtered and evaluated the growth performance parameters for the study of stocking density, chemical composition, cholesterol content, fatty acid profile, quality of lipid fraction in both studies. The liver of fish from the second stage of labor was frozen at - 80°C for lipid peroxidation analysis and determination of enzyme activity of oxidative stress (catalase and superoxide dismutase). It follows that for the study of stoking significant difference ρ <0.05 between the final average weight and total weight gain between the different densities tested, the highest weight was found in the group density of 75 fish/m3. The body composition analysis, differences were observed ρ <0.05 between the densities on moisture, total lipid content, protein, calories and cholesterol. The ratio polyunsaturated / saturated was higher in density of 11.76 for 100 fish/m3, since the density of 50 fish/m3 presented a sum of 6.85 for the levels of EPA + DHA. In assessing the nutritional quality of lipids, the densities studied showed the contents of n-6/n-3, hypocholesterolemic/hypercholesterolemic index of polyunsaturated fatty acids of atherogenicity and index of thrombogenicity as favorable for consumption. Fish reared at a density of 50 fish/m3 can be seen as a good food from a nutritional standpoint, they presented a good level of fatty acids, especially omega-3 fatty acid and its value in hypocholesterolemic/hypercholesterolemic. Regarding the second stage of labor was observed difference ρ<0.05 between the levels of vitamin C supplementation levels in total lipid content, crude protein, calories and cholesterol. The ratio polyunsaturated/saturated was higher in the supplementation level of 250 mg of vitamin C (1.26), since the level of 500 mg of vitamin C showed a sum of 6.48 for the levels of EPA + DHA. In assessing the nutritional quality of lipids, the levels of vitamin C study showed rates of n-6/n-3, hypocholesterolemic / hypercholesterolemic index of atherogenicity and index of thrombogenicity for subsequent food consumption. Fish reared with diets supplemented with 750 mg of vitamin C in the density of 50 fish/m3 can be seen as a good food from a nutritional standpoint, they presented a good level of fatty acids, especially omega-3 fatty acid and its value in hypocholesterolemic/hypercholesterolemic. In the study of redox balance results showed that there was an increase in lipid peroxidation, suggesting that there may have been damage to the liver of animals and the antioxidant defenses were not sufficient to prevent oxidative stress. Density of 50 fish/m3, the dietary supplementation with vitamin C can be pro-oxidant. Since the density 100 fish/m3, vitamin C supplementation may be an antioxidant. The catalase activity of the enzyme showed low activity, suggesting an impairment in hepatic redox balance for this enzyme in animals receiving diets containing different levels of vitamin C. Since superoxide dismutase activity of the enzyme showed high activity, suggesting a redox balance in protecting liver for this enzyme in animals receiving diets containing different levels of vitamin C.